VALIDASI METODE PENENTUAN KADAR PONCEAU 4R DALAM MINUMAN SUSU CAIR - Christianti, Vania
Milk beverages are popular because of their high nutritional value, and milk products that are enhanced with various fruit flavors are especially in high demand. Colorants are usually added to fruit flavored milk in order to increase its attraction and appearance. Ponceau 4R is one of synthetic food colorants, which is commonly used as food additives. However, the use of synthetic food colorants must be conducted in accordance with the applicable regulations because it can cause health issues, such as increased hyperactivity in children. Therefore, it is necessary to monitor synthetic food colorants in food/drinks consumed by the community. Maximum limit of food colorants in food/drink according to European Food Safety Authority (EFSA) is 50 mg/L. The aim of this study was to validate an analytical method for determination of Ponceau 4R in liquid milk products using Spectrophotometer UV-Vis. Validation method by using Ponceau 4R standard solution shows good linearity with r = 0.9992, Vxo = 0.805%, limit of detection is 0.604 ?g/mL, limit of quatification is 2.013 ?g/mL. Accuracy of recovery percentage within the range of 98.276 –101.682 %, coefficient variance for precision test intra day and inter days are 1.288 % and 1.549% respectively. In addition, validation method was also conducted for milk simulation containing Ponceau 4R, accuracy of recovery percentage is within the range of 81.094-86.393%, coefficient variance for intra day precision is 1.162%. Amount of Ponceau 4R in liquid milk sample A, B, C, D, E, F are 36.260, 35.993, 35.176, 35.827, 37.959, 34.8333 mg/L respectively.